2019
DOI: 10.1007/s40725-019-00091-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Impact Assessment of Forest Operations: a Review

Abstract: Purpose of Review One of the challenges of forest operations is to consider the consequences of different management strategies and to estimate the economic, environmental and social performance of different processes, products, or services. From the methods available to quantify the impact of alternative forest management, we selected the method of Sustainability Impact Assessment (SIA), an iterative process that includes the analysis of the societal, environmental, and economic sustainability pillars and off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…Recent studies have shown that that there are few studies related to FO considering all pillars of sustainability [38]. Most studies are focused only on either environmental or on economic and environmental aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that that there are few studies related to FO considering all pillars of sustainability [38]. Most studies are focused only on either environmental or on economic and environmental aspects.…”
Section: Discussionmentioning
confidence: 99%
“…In a modern and multifunctional forestry, in which society is asking for sustainable forestry and naturalistic forest management [7], FO should ideally be carried out in a sustainable manner and thus, support the concept of Sustainable Forest Management (SFM) [18,37,38]. It aims to improve economic, but also environmental and social performances of forest processes, products and/or ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…While retaining their crucial role, conventional statistics are increasingly bolstered by new analytical techniques better suited to reflect the complexity of the systems under investigation. As interest expanded beyond the productivity and cost of a single machine or team, so did the toolbox of the Forest Engineer, which has led to the widespread use of multi-criteria approaches, including Life Cycle Analysis (LCA) [18], sustainability impact assessment [19,20] and multi-criteria analysis [21]. As they reflect the complexity of strategic issues, the insights obtained with these methods are of specific interest to policy-makers, which illustrates a steady shift in terms of intended users.…”
Section: Disciplinary Integration To Adapt To the Changing Needs And mentioning
confidence: 99%
“…The environmental aspect of sustainable forestry development implies the preservation of the environment, the biological diversity of forest ecosystems, the rational use of natural resources, the protection of the atmosphere, land, subsoil, forests, water, and the ecologically safe use of biotechnology (Goals 6,12,13,15). The economic aspect reflects the balance of economic interests of the main subjects of forest relations: the state, the owner of the forests, forest users, the management authorities of forests at all levels and the public (Goals 2,3,7,8,12) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these environmental pressures may often remain external to the companies and would not be accounted for in such traditional performance measures as, e.g., financial indicators. The environmental measures (and the associated EPIs) can be measured in a number of ways [7][8][9]. In particular, EPIs are designed to describe such issues as pollution, biodiversity, climate, energy use, erosion, ecosystem services, and environmental education, among others [10,11].…”
Section: Introductionmentioning
confidence: 99%